Os novos municípios do estado do Tocantins, criados pós 1989 e os usos do território - Santos, Robson Francisco Barros Dos (Universidade Federal do Tocantins, 2020)
This dissertation studies the use of the territory in the new municipalities of the state of Tocantins. This state was created due to economic abandonment in relation to the former south of Goiás. With the promulgation of the 1988 Brazilian Constitution, new guarantees were proposed, influencing the uses of the state by hegemonic and hegemonized actors. This study turned to the new municipalities in the light of Milton Santos's theory of the territory used. The territory is used by everything and by everyone, by those who have more use capacity (the hegemonic actors) and by those who do not have such capacity (the hegemonized actors), that is, that has the territory as shelter. Considering the creation of Tocantins, the questions guiding the work were the following: what has changed in the municipalities? Did the creation of the state resulted in more support? What structures were created? The analysis, which focused on how each agent uses the territory, was based on maps to verify the inequalities of uses in the new municipalities. The finding was that these latter do not fulfill their real role as a federative members because they have many needs.